A new BaAl2O4-YAG: Ce composite ceramic phosphor for white LEDs and LDs lighting. Issue 7 (July 2021) - Tian, Yanna; Chen, Jie; Yi, Xuezhuan; Zhao, Di; Weng, Zixin; Tang, Yanru; Lin, Hui; Zhou, Shengming
Abstract: A new BaAl2 O4 -YAG: Ce composite ceramic phosphor (CCP) was prepared and studied as the color conversion materials for high-efficiency white LEDs/LDs lighting. It was discovered that the grain growth of YAG can be remarkably restrained by the introduction of BaAl2 O4 second phase, which brought about a small and uniform distribution of YAG particles. 10 wt% BaAl2 O4 -YAG: Ce CCP presents excellent luminescent performances with a maximum luminous efficacy (LE) of 150 lm/W under the excitation of blue LEDs. When excited by blue LDs with an input power of 13.44 W, 20 wt% BaAl2 O4 -YAG: Ce CCP shows no luminescent saturation and its maximum luminous flux (LF) is up to 479 lm. Compared to pure YAG: Ce CCPs, BaAl2 O4 -YAG: Ce CCP has better luminescent characters, which manifests its great application potential in high brightness white LEDs/ LDs lighting.